Transformation of Character Education Based on THK for Elementary School Students in the Digital Era - Sumarjono, Kadek Jefry Dwi; Ariyana, Komang Agus; Riani, Luh; Yasa, I Gede Windu; Lesmana, Kadek Yogi Parta (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to determine the meaning of Character Education, Tri Hita Karana, Digitalization, and the transformation of character education based on Tri Hita Karana in elementary schools in the digital era. The meaning of Education. Education